Beyond Ingroup Love: A Systematic Review of the Antecedents and Consequences of Collective Narcissism - Tondang, Edoardo; Ariestina, Selly; Ibrahim, Muhammad Buchori; Fadesti, Pralayar Fanny; Lubis, Hairani (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Collective narcissism, a form of group identification defined by an exaggerated belief in the ingroup’s unrecognized greatness and a defensive need for external validation, is a significant area of social psychological inquiry. While research has grown since its formal conceptualization, a comprehensive synthesis is needed. This systematic review, adhering to PRISMA guidelines, synthesizes empirical findings from 24 studies identified via Scopus concerning the antecedents and consequences of collective narcissism. Findings reveal that collective narcissism is influenced by both individual-level factors—such as individual narcissism, low or unstable self-esteem, need for uniqueness, and Dark Triad-related personality traits—and contextual factors, including perceived intergroup threat, political orientation, lower levels of globalization, and culturally embedded historical narratives. In turn, this form of group identification consistently predicts a wide range of negative outcomes. These include intergroup hostility, prejudice, aggressive behaviors, support for populist and authoritarian political positions, conspiracy belief endorsement, and detrimental intragroup dynamics, such as objectification and reduced psychological well-being. The review underscores the importance of distinguishing collective narcissism from secure ingroup identification, highlighting its uniquely defensive and compensatory mechanisms. Implications for theory and practice are discussed, with recommendations for future longitudinal and experimental studies to clarify causal pathways and inform interventions. Overall, our synthesis contributes to a deeper understanding of how collective narcissism fuels intergroup conflict and undermines societal cohesion.